Optimization of Growing Media to Support Microgreens Growth and Nutritional Profile - Sukewijaya, I Made; Dwiyani, Rindang; Bimantara, Putu Oki (Universitas Panji Sakti, 2025)
Microgreens are young seedlings of edible vegetables, herbs, and flowers. Growing media plays a vital role in plant growth and the biosynthesis of multiple metabolites that improve the nutritional profile of microgreen. This study evaluated the effect of growing media from a combination of soil, husk charcoal, and perlite with a specific ratio of 1:1:1 (TAP 111), 2:1:1 (TAP 211), 1:2:1 (TAP 121), and 1:1:2 (TAP 112) on the nutrition profile and fresh weight of several microgreen plants, including water spinach, red spinach, green mustard, red lettuce, green spinach, and bok choy. The nutrient contents of nitrogen, phosphorus, and potassium in the growing media were quantified in this study. The data analysis was performed using Duncan’s multiple range test to assess the quantity of vitamin A, vitamin C, antioxidant capacity, and fresh weight at a 5% confidence level. The results showed that TAP121 media exhibited moderate levels of nitrogen (0.23%), very high phosphorus (238.68 ppm), and high potassium (324.69 ppm. The highest vitamin A was found in red spinach in TAP111 (27.77 mg 100 g-1) and TAP112 (22.72 mg 100 g-1) media. The highest vitamin C was found in green mustard in TAP111 media (66.44 mg 100 g-1) and in bok choy in TAP112 media (61.25 mg 100 g-1). The highest antioxidant capacity was found in Bok choy in TAP121 media (386.4 mg AAEAC 1000 g-1) and the highest fresh weight was found in water spinach in TAP121 media (4.03 g). In conclusion, TAP121 media can be recommended to support the balanced growth and nutritional quality of microgreen plants, especially bok choy, and water spinach. This study provides insights into how specific combinations of growing media can enhance the growth and nutritional content of microgreens. Future studies could focus on optimizing nutrient levels and environmental conditions to maximize the antioxidant properties and other bioactive compounds in microgreens.